Relevansi Pemikiran Al-Faruqi tentang Islamisasi Ilmu Pengetahuan dalam Bidang Ekonomi: The Relevance of Al-Faruqi’s Thought on the Islamization of Knowledge in the Field of Economics - Ahmadiono Ahmadiono (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2005)
The Islamic revival in the 20th century gave rise to the discourse on the Islamization of knowledge as a response to the civilizational crisis caused by Western secular dominance. Isma'il Raji al-Faruqi proposed a systematic framework based on five principles of tawhid to reconstruct modern knowledge in accordance with the Islamic worldview. This article analyzes the relevance of al-Faruqi's thought for developing Islamic economics. Through library research and critical analysis of al-Faruqi's twelve-step work plan, the article finds that conventional economics is grounded in materialism, individualistic rationalism, and positivism, which contradict Islamic values of tawhid, khilafah, and justice. The findings indicate that the Islamization of economics requires mastery of modern economics, comprehension of Islamic intellectual heritage, and their synthesis to produce an alternative paradigm. In conclusion, al-Faruqi's thought holds strong methodological relevance for constructing a just and ethical Islamic economics. Kebangkitan Islam pada abad ke-20 memicu wacana islamisasi ilmu pengetahuan sebagai respons terhadap krisis peradaban akibat dominasi sekularisme Barat. Isma'il Raji al-Faruqi menawarkan kerangka sistematis berbasis lima prinsip tauhid untuk merekonstruksi pengetahuan modern agar selaras dengan pandangan dunia Islam. Artikel ini bertujuan menganalisis relevansi gagasan al-Faruqi dalam membangun ekonomi Islam. Melalui studi kepustakaan dan analisis kritis terhadap dua belas langkah kerja al-Faruqi, ditemukan bahwa ekonomi konvensional bertumpu pada asumsi materialisme, rasionalisme individualis, dan positivisme yang bertentangan dengan nilai tauhid, khilafah, dan keadilan Islam. Hasil penelitian menunjukkan bahwa islamisasi ekonomi memerlukan penguasaan ilmu ekonomi modern, pemahaman khazanah Islam, serta sintesis keduanya untuk melahirkan paradigma alternatif. Kesimpulannya, pemikiran al-Faruqi memiliki relevansi kuat sebagai landasan metodologis dalam membangun ekonomi Islam yang etis dan berkeadilan.